2015
DOI: 10.1089/neu.2014.3661
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Resting-State Brain Sensorimotor Connectivity following Spinal Cord Injury: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: Motor and sensory deficits after spinal cord injury (SCI) result in functional reorganization of the sensorimotor network. While several task-evoked functional magnetic resonance imaging (fMRI) studies demonstrated functional alteration of the sensorimotor network in SCI, there has been no study of the possible alteration of resting-state functional connectivity using resting-state fMRI. The aim of this study was to investigate the changes of brain functional connectivity in the sensorimotor cortex of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 27 publications
2
45
0
1
Order By: Relevance
“…They consider the finding as evidence of dynamic reshaping in the reorganized M1 (34). We have taken this observation further, suggesting that in a clinical population, remote effects may also be different, especially with concomitant connectivity alterations (26,51,52). Thus, if rTMS of the standard hotspot fails to induce pain relief, stimulation of an external reorganized site may afford a more positive response, as our results show.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…They consider the finding as evidence of dynamic reshaping in the reorganized M1 (34). We have taken this observation further, suggesting that in a clinical population, remote effects may also be different, especially with concomitant connectivity alterations (26,51,52). Thus, if rTMS of the standard hotspot fails to induce pain relief, stimulation of an external reorganized site may afford a more positive response, as our results show.…”
Section: Discussionsupporting
confidence: 66%
“…In 2006 Lefaucheur and colleagues described pain relief from rTMS over M1 facial representation in patients with arm pain, and arm representation in facial pain, but their trial was based on single sessions only, with uncertainty of the generalizability of the results in clinical practice . In addition, their patients included those with poststroke pain in whom cortical rearrangement would likely be substantial . To our knowledge, our study is the first to demonstrate the relevance of using cortical reorganisation to target rTMS treatment for neuropathic pain.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…clude the precentral gyrus, postcentral gyrus, and supplementary motor area. Using seed-based methods to identify the SMN, Liu et al 17 and Min et al 22 found an absence of motor area activity on the side contralateral to the limb affected by BPI. Liu et al 17 found decreased interhemispheric rsFC between motor cortices in patients with BPI.…”
Section: Discussionmentioning
confidence: 99%
“…The resting‐state functional magnetic resonance imaging (rsfMRI), a neuroimaging technology to measure functional connectivity of multiple brain regions (Sakoğlu et al, ), is incorporated in the strategy. In the last decade, rsfMRI has detected abnormal functional connectivity, which is possibly associated with pathophysiology of chronic pain, in patients with neuropathic pain (Mills et al, ), arthritis (Howard et al, ), spinal cord injury (Kaushal et al, ; Min et al, ) and fibromyalgia (Napadow, & Harrisis, ; Schmidt‐Wilcke et al, ) and also in rat pain models with etiology of peripheral neuropathy (Baliki, Chang, Baria, Centeno, & Apkarian, ; Chang et al, ), arthritis (Abaei et al, ) and spinal cord injury (Seminowicz et al, ). Currently, rsfMRI is considered as a useful tool for exploration of pathophysiology of central nervous system (CNS) diseases including pain (Sakoğlu et al, ) and translation between animals and humans (Bajic, Craig, Mongerson, Borsook, & Becerra, ; Pan, Billings, Grooms, Shakil, & Keilholz, ).…”
Section: Introductionmentioning
confidence: 99%